Determining optimum electro discharge machining parameters for drilling of a small hole by utilizing taguchi method - Saiful Bahri, Mohamed; M.K.A.M., Ariffin; Hazami, Che Hussain (2014)
Electro discharge machining (EDM) is a preens that uses an electric sparks to generate the high temperature and melt the workpiece. One of the EDM prows; is drilling. In EDM chilling an electro thermal mechanism is introduced between the electrode and node piece to create the hole. The hole size is dependent on the diameters of electrode used during the drilling process. The present study performs Taguchi method to investigate the optimal process parameters for high. speed EDM super drill machine that is used to make a small hole. The norkpicoe used is made from lithrium alloy (Ti-6: ASTM 11348 Grade 5) and the copper electrode is 2.0 awn in diameter. In this experiment, the process inrameters that were selected to be optimised ate: current pulse off, maximum current and standard %ukase resets. An orthogonal away L. were employed to analyze the hole enlargement and material removal rate (MR) depending on 2.0 mm diameter hole penetration The optimum EDM parameters for hale making process was established and sallied with the acquired results.